Existing German translations of the epic by Rustaveli - Steffi Chotiwari-Junger, (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2014)
The present article discusses the poetic and prosaic German translations of The Man in the Panther Skin by Shota Rustaveli, namely, translations by Arthur Leist, Hugo Huppert, Ruth Neukomm, Michael Tseretheli, Hermann Buddensieg and Marie Prittwitz.